Impact of Priming on Effectiveness of TMS in Detecting Language-eloquent Brain Areas in Tumor Patients - Freigang, Sascha; Fresnoza, Shane; Mahdy Ali, Kariem; Zaar, Karla; Jehna, Margit; Reishofer, Gernot; Rammel, Katrin; Studencnik, Fritz; Ischebeck, Anja; von Campe, Gord (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Background and Study Aims Language is characteristically human, and preserving it is critical when resecting tumors in language-eloquent brain areas. Navigated repetitive transcranial magnetic stimulation (nrTMS) has been used in recent years as a noninvasive technique to identify preoperatively the language-eloquent cortical areas in tumor patients. An important objective is to increase the sensitivity and specificity of nrTMS in detecting language-related areas and increase the positive correlation of its results to that of intraoperative direct cortical stimulation (DCS). Although the technical aspects of the procedure have received enormous interest, factors related to the targeted cortical area such as previous cortical history or activity have been neglected. Therefore, the present study explores the impact of previous cortical history or activity on the effectiveness of a subsequent nrTMS mapping paradigm.Materials and Methods Twelve right-handed patients with a left hemispheric glioma underwent presurgical nrTMS language mapping and intraoperative language mapping with DCS. nrTMS was performed using a continuous theta burst stimulation paradigm to inhibit possible language relevant areas in the vicinity of the tumor, determined anatomically or based on functional magnetic resonance imaging hotspots. The nrTMS was applied in two separate sessions. One of the sessions randomly included a priming paradigm to precondition the targeted cortical areas.Results Priming stimulation decreased the error detection of the subsequent nrTMS mapping paradigm. This effect was more robust on major types of errors such as speech arrest and hesitation.Conclusion Prior cortical activity as induced by the priming stimulation has a profound impact on the responsiveness to the nrTMS mapping paradigm. Our findings further showed that metaplasticity, a type of homeostatic plastic process, could be elicited even in cortical areas affected by a growing tumor.
Keywords: language mapping; repetitive transcranial magnetic stimulation; direct cortical stimulation; tumor patient; plasticity